Galen's theory of black bile : Hippocratic tradition, manipulation, innovation - Stewart, Keith Andrew, (Studies in Ancient Medicine, 2018)
In Galen's Theory of Black Bile: Hippocratic Tradition, Manipulation, Innovation Keith Stewart investigates Galen's writing on black bile to explain health and disease and shows that Galen sometimes presented this humour as three substances with different properties that can either be harmful or beneficial to the body. Keith Stewart analyses the most important treatises for Galen's physical description and characteristion of black bile and challenges certain views on the development of this humour, such as the importance of the content of the Hippocratic On the Nature of Man . This analysis allows us to understand how and why Galen defines and uses black bile in different ways for his arguments that cannot always be reconciled with the content of his sources.